Clinical Predictive Factors for Reproductive Organ Involvement in Females with Muscle Invasive Bladder Cancer: A Retrospective Review of Radical Cystectomy Cases from Two Tertiary Centers - Nastaran Mahmoudnejad; Mohammad Hamidi Madani; Parham Montazeri; Kimia Vakili; Mohammad Nasri; Sajjad Imen; Navid Masoumi (Iranian Journal of Medical Sciences)
Background: The preservation of reproductive organs in females with muscle-invasive bladder cancer (MIBC) might improve reproductive and sexual function. This study aimed to identify potential clinical risk factors for reproductive organ involvement (ROI) using preoperative data from transurethral resection of tumor (TURT) reports and imaging findings. Methods: This retrospective analysis was conducted on 143 women with bladder cancer who underwent radical cystectomy (RC) at Modarres and Labafinejad Medical Centers in Tehran, Iran, between 2010 and 2019. Demographic, clinical, and pathological data, along with follow-up reports, were collected from medical records and analyzed.Results: The mean age of the participants was 69.17±10.62 years, with an ROI rate of 16.8%. The vagina was the predominantly involved organ. Significant independent risk factors for ROI included clinical T stage (P=0.042), bladder neck or trigonal location of the tumor (P<0.001), tumor size> 5 cm (P=0.002), presence of carcinoma in situ (CIS) (P=0.014), lymphovascular invasion in TURT reports (P=0.002), and preoperative hydronephrosis in imaging (P<0.001). Patients with ROI demonstrated significantly lower 5-year survival rates than those without ROI, with overall survival rate of 20.8% versus 63.9% and cancer-specific survival rate of 19% versus 64.8%, respectively. Conclusion: This study represented a comprehensive analysis of preoperative TURT and imaging predictors of ROI.  Clinical T stage, tumor location, maximum tumor size, concomitant CIS, presence of lymphovascular invasion, and hydronephrosis were identified as significant preoperative clinical factors associated with ROI. These findings might help guide surgical planning for organ preservation in female MIBC patients.